On the history of the monastery of Zhwa-lu : begin the texts of the Zhwa lu gdan rabs and the autobiography - Blo-gsal-bstan-skyoṅ, Źwa-lu Ri-sbug-Sprul-sku, 1804- (Smanrtsis shesrig spendzod, 1971)
History of a monastery in Tsang, Tibet, and the subsect of Buddhism which developed there.